Preparation method and application of cellulose solution
The high cost and stability of cellulose dissolution method are solved by the organic alkali-COS-organic solvent system, and the multi-field application of functional materials is realized.
Patent Information
- Application Number
- CN202411514132.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The existing cellulose dissolution methods have problems such as high cost, complex processes, poor dissolution stability and limited functionality, which are difficult to meet the multifunctional needs of new polymer materials.
Cellulose dissolution is performed using a mixed system of organic alkali-COS-organic solvents. The mixture in the reactor is heated to obtain a stable cellulose solution, and the solution is used to react in series with acrylate compounds to prepare sulfur-containing cellulose function. Material.
It has achieved cost reduction, process simplification, stability improvement and functional expansion of cellulose dissolution, and is suitable for wastewater treatment, biomedicine, electronics industry and coatings industry.
Smart Images

Figure CN119241872A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for dissolving cellulose and its application, in particular to a method for dissolving cellulose by using an organic alkali-COS-organic solvent dissolving system and the application of a cellulose solution. Background Art
[0002] As one of the important materials that promote the development of human civilization, polymer materials have played a very important role in the development of modern human civilization. However, most traditional polymer materials are extracted from petroleum. Their large-scale use not only leads to a huge consumption of non-renewable resources, but also puts considerable pressure on the environment. Research on the preparation of sustainable new polymer materials using plants as raw materials has attracted much attention.
[0003] Cellulose is the main component of plant cell walls and an inexhaustible bio-renewable resource in nature. Because it is renewable, cheap, biodegradable, easy to modify the fiber surface, has good mechanical properties and low density, it is of great significance to use the natural polymer skeleton of cellulose to construct new green polymer materials to promote the sustainable development of human society.
[0004] In the application of building new green polymer materials, dissolving cellulose to obtain cellulose solution is a necessary prerequisite. However, due to the large number of hydrogen bonds between molecules and within molecules in the structure of cellulose, cellulose cannot be melt-processed and is insoluble in water and traditional organic solvents. Therefore, the research and development of cellulose dissolution systems has attracted the attention of many researchers.
[0005] The traditional methods for dissolving cellulose mainly include the viscose method, the copper ammonia method, the cadmium / ethylenediamine solution, the lithium chloride / dimethylacetamide method, the 4-methylmorpholine-N-oxide (NMMO), the NaOH / CS2 and the carbamate solvent method. In addition, the research results in recent years have shown that cellulose also has a good dissolution effect in new ionic liquids, sodium hydroxide / urea aqueous solution and CO2-based reversible solvent systems.
[0006] However, these traditional cellulose dissolution methods still have certain problems in practical application, for example: the preparation cost of ionic liquids is relatively high, and the production cost will be increased during the preparation process. In addition, the recovery of ionic liquids requires complex processes and equipment. The dissolution of cellulose in the alkali / urea aqueous solution system generally needs to be carried out at sub-zero temperatures, so the dissolution conditions are relatively harsh. Furthermore, the stability of the solution in the alkali / urea aqueous solution system is affected by external factors such as temperature and stirring, and there is a problem of poor dissolution stability. Although the CO2-based reversible solvent system has a low cost, relatively simple post-treatment, and high dissolution stability, its dissolution system has a relatively large viscosity. In subsequent applications, its dispersibility in the reaction system is poor and the reaction rate is slow. In addition, the function of cellulose dissolved by the CO2-based reversible solvent system is limited and cannot meet the needs of cellulose multifunctional derivatization. For example, when preparing sulfur-containing cellulose derivatives, it is necessary to first dissolve the cellulose and then carry out a thiol reaction to obtain sulfur-containing cellulose.
[0007] Based on this, researching and developing different cellulose dissolution methods to reduce its dissolution cost, simplify the dissolution process, improve dissolution stability, facilitate subsequent applications and expand its functionality are of great significance for further expanding the application of cellulose in the field of new polymer materials. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a method for preparing a cellulose solution and an application of the cellulose solution. The cellulose dissolution method of the present invention has the characteristics of simple process, low cost, easy post-treatment, good dissolution stability, low viscosity of the dissolution system and convenient subsequent application; in addition, the cellulose solution of the present invention can obtain sulfur-containing cellulose derivative functional materials without undergoing thiol reaction in the subsequent derivatization application process, which can be used in wastewater treatment, biomedicine, electronics industry and coating industry, etc. This method is of great significance for promoting the derivatization application of cellulose.
[0009] One of the technical solutions of the present invention:
[0010] Provided is a method for preparing a cellulose solution, which uses a mixture of an organic base, COS and an organic solvent as a dissolving system to dissolve cellulose.
[0011] Preferably, the method for preparing the cellulose solution comprises the following steps:
[0012] (1) mixing cellulose, an organic base and an organic solvent to obtain a mixture;
[0013] (2) placing the mixed material in a reaction kettle, filling it with COS gas and sealing it;
[0014] (3) heating the sealed reactor to react the mixture therein, and obtaining a cellulose solution after the reaction is completed.
[0015] Preferably, in the aforementioned method for preparing a cellulose solution, the cellulose is one of microcrystalline cellulose, cotton, wood pulp, bamboo pulp or straw cellulose, or a combination of any of them.
[0016] Preferably, in the aforementioned method for preparing a cellulose solution, the cellulose has the following general chemical structure formula:
[0017]
[0018] Among them, 50﹤n-4﹤1000.
[0019] Preferably, in the aforementioned method for preparing a cellulose solution, the organic base is any one of the following structures:
[0020]
[0021] Wherein: R is independently H, methyl or ethyl; R1 is independently H or -CH3; R2, R3, R4 and R5 are independently H or alkyl with 1-6 carbon atoms.
[0022] Preferably, in the aforementioned method for preparing a cellulose solution, the organic solvent is one of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylimidazolidinone, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide or N,N-dimethylpropylene urea, or a mixture of any of them.
[0023] Preferably, in the aforementioned method for preparing cellulose solution, in the mixed material of step (1), the mass concentration of cellulose is 1-20%, the mass concentration of organic base is 0.5-30%, and the balance is organic solvent.
[0024] Preferably, in the aforementioned method for preparing the cellulose solution, in the closed reactor in step (2), the pressure of the COS gas is 0.2-5 MPa.
[0025] Preferably, in the aforementioned method for preparing the cellulose solution, the final temperature of the heating in step (3) is 30-70° C., and the reaction time is 2-6 hours.
[0026] The second technical solution of the present invention:
[0027] Provided is a cellulose solution, which is prepared according to the above method.
[0028] The third technical solution of the present invention:
[0029] Provided is a sulfur-containing cellulose functional material, which is prepared using the aforementioned cellulose solution and an acrylate compound as raw materials, wherein the acrylate compound is any one of the following compounds:
[0030]
[0031] Wherein: R is independently -CH3 or an alkyl group with 1-6 carbon atoms.
[0032] Preferably, the aforementioned sulfur-containing cellulose functional material is prepared by adding an acrylate compound to the cellulose solution, reacting at 25-35°C for 1-3h, then adding the reaction product to anhydrous ethanol, stirring to obtain a precipitate, and finally filtering out the precipitate, washing it with ethanol, and then drying it to obtain a heavy metal ion adsorbent in the solution.
[0033] Preferably, in the aforementioned sulfur-containing cellulose functional material, when an acrylic ester compound is added to the cellulose solution, the molar ratio of the glucose unit in the cellulose solution to the C=C bond in the acrylic ester compound is 1:1-3.
[0034] The fourth technical solution of the present invention:
[0035] Provided is an application of the aforementioned sulfur-containing cellulose functional material in the fields of wastewater treatment, biomedicine, electronics industry and coating industry.
[0036] Beneficial effects of the present invention:
[0037] 1. The dissolution system adopted in the cellulose dissolution method of the present invention is a mixed system of organic alkali, COS and organic solvent. This system is different from the existing cellulose dissolution system and is a brand-new dissolution system.
[0038] 2. The dissolution system used in the cellulose dissolution method of the present invention has low cost, simple process, and easy post-treatment, which has natural advantages in promoting the industrial application of the dissolution system of the present invention.
[0039] 3. When the dissolution system used in the cellulose dissolution method of the present invention is actually used, the obtained cellulose solution is more stable and the industrial application is more worry-free.
[0040] 4. The cellulose solution obtained by the dissolution method of the present invention has a lower viscosity, which is helpful to accelerate the diffusion speed of the raw materials and shorten the reaction time in the subsequent multi-component reaction.
[0041] 5. The sulfur-containing cellulose functional material prepared by a series reaction of the cellulose solution obtained by the dissolution method of the present invention with an acrylic acid ester compound can be used in the fields of wastewater treatment, biomedicine, electronics industry and coating industry. This method is of great significance for promoting the application of cellulose derivatization. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a polarizing microscope photograph of microcrystalline cellulose dissolved by COS at 30°C for 4 hours after being pressurized with 1.0 MPa. It can be seen from the polarizing microscope photograph that microcrystalline cellulose (MCC) is completely dissolved, which fully demonstrates that the new DBU / COS / DMSO dissolution system has a good solubility for cellulose under this condition.
[0043] Figure 2 The XRD comparison diagram of dissolved microcrystalline cellulose and pure cellulose after being reacted at 30℃ for 4 hours with 1.0MPa COS pressed in; from the microcrystalline cellulose (MCC) that has not been dissolved, it can be observed that obvious characteristic diffraction peaks appear at 2θ=15.3°, 22.4° and 34.3°, proving that the crystal structure of the original MCC belongs to cellulose type I. On the contrary, under this condition, the regenerated cellulose (R-MCC) obtained by dissolving and reprecipitating MCC using the dissolution system of the present invention only has a relatively wide single characteristic diffraction peak at 2θ=19.64°, indicating that the MCC after dissolution and regeneration belongs to an amorphous structure, and the crystal structure of MCC after dissolution has completely changed.
[0044] Figure 3 is the real-time infrared spectrum of cellulose dissolution; from the real-time infrared spectrum, we can know that as the reaction time increases, NH + (2350~2650cm -1 )、C=O(1550~1700cm -1 )、COR(1160~1260cm -1 ) and NH(840~760cm -1 ) was significantly enhanced, and the peak intensity did not change when the reaction time was extended to 4 h, indicating that cellulose can be completely dissolved after being subjected to a pressure of 1.0 MPa and reacting at 30 °C for 4 h.
[0045] Figure 4 The figure is a comparison of rheological tests of 5 wt% cellulose dissolved in the DBU / CO2 / DMSO system and the organic base-COS-organic solvent system of the present invention. It can be clearly observed from the figure that the cellulose solution dissolved by the dissolving system of the present invention exhibits a dilute solution phenomenon, which is a typical Newtonian fluid behavior; while the apparent viscosity of the cellulose solution dissolved by the DBU / CO2 / DMSO system increases, and the solution exhibits shear thinning in the low shear rate region. The concentration of the cellulose solution increases, indicating that the interaction between molecules becomes stronger. DETAILED DESCRIPTION
[0046] The present invention will be further described below in conjunction with the embodiments, but they are not intended to limit the present invention.
[0047] Embodiments of the present invention
[0048] The "COS" mentioned in the present invention is carbonyl sulfide.
[0049] Embodiment 1:
[0050] Weigh 1 g of microcrystalline cellulose, 2.828 g of 1,8-diazabicyclo[5.4.0]-7-undecene (DBU) and 15.367 g of dimethyl sulfoxide (DMSO) into the reactor, and cover the reactor;
[0051] The reactor was charged with COS gas at 0.2 MPa, and then heated to 30°C and stirred for 2 h to obtain a homogeneous cellulose solution.
[0052] Embodiment 2:
[0053] The mixture system in the reactor of this embodiment is the same as that in embodiment 1;
[0054] The difference is that in this embodiment, COS gas at 0.5 MPa is charged into the reactor, and then the reactor is heated to 30° C. and stirred for reaction for 2 hours to obtain a homogeneous cellulose solution.
[0055] Embodiment 3:
[0056] The mixture system in the reactor of this embodiment is the same as that in embodiment 1;
[0057] The difference is that in this embodiment, COS gas at 1.0 MPa is charged into the reactor, and then the reactor is heated to 30° C. and stirred for 2 hours to obtain a homogeneous cellulose solution.
[0058] Embodiment 4:
[0059] The mixture system in the reactor of this embodiment is the same as that in embodiment 1;
[0060] The difference is that in this embodiment, 3.0 MPa of COS gas is charged into the reactor, and then the reactor is heated to 30° C. and stirred for reaction for 2 hours to obtain a homogeneous cellulose solution.
[0061] Embodiment 5:
[0062] The mixture system in the reactor of this embodiment is the same as that in embodiment 1;
[0063] The difference is that in this embodiment, COS gas at 5.0 MPa is charged into the reactor, and then the reactor is heated to 30° C. and stirred for reaction for 2 hours to obtain a homogeneous cellulose solution.
[0064] Embodiment 6:
[0065] The mixture system in the reactor of this embodiment is the same as that in embodiment 1;
[0066] The difference is that in this embodiment, COS gas at 0.2 MPa is charged into the reactor, and then the reactor is heated to 30° C. and stirred for 4 hours to obtain a homogeneous cellulose solution.
[0067] Embodiment 7:
[0068] The mixture system in the reactor of this embodiment is the same as that in embodiment 1;
[0069] The difference is that in this embodiment, COS gas at 0.5 MPa is charged into the reactor, and then the reactor is heated to 30° C. and stirred for 4 hours to obtain a homogeneous cellulose solution.
[0070] Embodiment 8:
[0071] The mixture system in the reactor of this embodiment is the same as that in embodiment 1;
[0072] The difference is that in this embodiment, 1.0 MPa of COS gas is charged into the reactor, and then the reactor is heated to 30° C. and stirred for reaction for 4 hours to obtain a homogeneous cellulose solution.
[0073] Embodiment 9:
[0074] The mixture system in the reactor of this embodiment is the same as that in embodiment 1;
[0075] The difference is that in this embodiment, COS gas at 3.0 MPa is charged into the reactor, and then the reactor is heated to 30° C. and stirred for 4 hours to obtain a homogeneous cellulose solution.
[0076] Embodiment 10:
[0077] The mixture system in the reactor of this embodiment is the same as that in embodiment 1;
[0078] The difference is that in this embodiment, COS gas at 5.0 MPa is charged into the reactor, and then the reactor is heated to 30° C. and stirred for reaction for 4 hours to obtain a homogeneous cellulose solution.
[0079] Embodiment 11:
[0080] The mixture system in the reactor of this embodiment is the same as that in embodiment 1;
[0081] The difference is that in this embodiment, 1.0 MPa of COS gas is charged into the reactor, and then the reactor is heated to 50° C. and stirred for reaction for 4 hours to obtain a homogeneous cellulose solution.
[0082] Embodiment 12:
[0083] The mixture system in the reactor of this embodiment is the same as that in embodiment 1;
[0084] The difference is that in this embodiment, COS gas at 3.0 MPa is charged into the reactor, and then the reactor is heated to 50° C. and stirred for 4 hours to obtain a homogeneous cellulose solution.
[0085] Embodiment 13:
[0086] The mixture system in the reactor of this embodiment is the same as that in embodiment 1;
[0087] The difference is that in this embodiment, 1.0 MPa of COS gas is charged into the reactor, and then the reactor is heated to 70° C. and stirred for reaction for 4 hours to obtain a homogeneous cellulose solution.
[0088] Embodiment 14:
[0089] The mixture system in the reactor of this embodiment is the same as that in embodiment 1;
[0090] The difference is that in this embodiment, COS gas at 3.0 MPa is charged into the reactor, and then the reactor is heated to 70° C. and stirred for 4 hours to obtain a homogeneous cellulose solution.
[0091] Embodiment 15:
[0092] The mixture system in the reactor of this embodiment is the same as that in embodiment 1;
[0093] The difference is that in this embodiment, COS gas at 1.0 MPa is charged into the reactor, and then the reactor is heated to 30° C. and stirred for 6 hours to obtain a homogeneous cellulose solution.
[0094] After the reaction of Example 1-15 was completed, the COS in the reactor was released, and then the microscopic morphology of the cellulose solution therein was observed with polarized light. The relevant results are shown in Table 1 below:
[0095] Table 1
[0096]
[0097]
[0098] Note: “-” indicates incomplete dissolution, “+” indicates complete dissolution
[0099] The results fully demonstrate that cellulose can be completely dissolved when the reaction pressure is >0.5MPa, time is >4h and temperature is <50°C.
[0100] Embodiment 16:
[0101] Weigh 5 wt % of microcrystalline cellulose, 10 wt % of 1,8-diazabicyclo[5.4.0]-7-undecene (DBU), and the balance of dimethyl sulfoxide (DMSO), mix them, add them into the reactor, and cover the reactor;
[0102] 1.0 MPa of COS gas was charged into the reactor and stirred for reaction at 30° C. for 4 h to obtain a homogeneous cellulose solution.
[0103] Embodiment 17:
[0104] The reaction conditions of this example are consistent with those of Example 12;
[0105] The difference is that in this example, 15 wt % of 1,8-diazabicyclo[5.4.0]-7-undecene (DBU) is weighed.
[0106] Embodiment 18:
[0107] The reaction conditions of this example are consistent with those of Example 12;
[0108] The difference is that in this example, 20 wt % of 1,8-diazabicyclo[5.4.0]-7-undecene (DBU) is weighed.
[0109] Embodiment 19:
[0110] The reaction conditions of this example are consistent with those of Example 12;
[0111] The difference is that in this example, 10 wt % of 1,5-diazabicyclo[4.3.0]non-5-ene (DBN) is weighed.
[0112] Embodiment 20:
[0113] The reaction conditions of this example are consistent with those of Example 12;
[0114] The difference is that: in this embodiment, 10 wt % of triethylamine (TEA) is weighed.
[0115] The COS gas in the reaction kettle of Examples 16-20 was released, and then the microscopic morphology of the cellulose solution was observed using polarized light. The relevant results are shown in Table 2 below:
[0116] Table 2
[0117] serial number Cellulose content wt% Organic base and content wt% Organic solvents polarized light 16 5 10wt%DBU DMSO + 17 5 15wt%DBU DMSO + 18 5 20wt%DBU DMSO + 19 5 10wt%DBN DMSO - 20 5 10wt%TEA DMSO -
[0118] Note: “-” indicates incomplete dissolution, “+” indicates complete dissolution
[0119] The results fully demonstrate that the use of DBU with a strong alkalinity as a solvent (mass fraction ≥ 10wt%) has a good dissolution effect on cellulose. In addition, when the same mass fraction of organic base is added, the dissolution effect of DBU is better than that of DBN and TEA.
[0120] Embodiment 21:
[0121] Weigh 1 g of microcrystalline cellulose, 2.828 g of an organic base 1,8-diazabicyclo[5.4.0]-7-undecene (DBU), and then weigh 15.367 g of an organic solvent dimethyl sulfoxide (DMSO), respectively, mix them, add them into the reactor, and cover the reactor;
[0122] 1.0 MPa of COS gas was charged into the reactor and stirred for reaction at 30° C. for 4 h to obtain a homogeneous cellulose solution.
[0123] Embodiment 22
[0124] The reaction conditions of this example are consistent with those of Example 17;
[0125] The difference is that the organic solvent added in this embodiment is N,N-dimethylformamide (DMF).
[0126] Embodiment 23
[0127] The reaction conditions of this example are consistent with those of Example 17;
[0128] The difference is that the organic solvent added in this embodiment is N,N-dimethylacetamide (DMAc).
[0129] Embodiment 24
[0130] The reaction conditions of this example are consistent with those of Example 17;
[0131] The difference is that the organic solvent added in this embodiment is N-methylpyrrolidone (NMP).
[0132] The COS gas in the reaction kettle of Examples 21-24 was released, and then the microscopic morphology of the cellulose solution was observed using polarized light. The relevant results are shown in Table 3 below:
[0133] Table 3
[0134] serial number Cellulose content wt% Organic base Organic solvents polarized light 21 5 DBU DMSO + 22 5 DBU DMF - 23 5 DBU DMAc - 24 5 DBU NMP -
[0135] Note: “-” indicates incomplete dissolution, “+” indicates complete dissolution
[0136] The results fully demonstrate that when DMSO with a higher polarity is used as the solvent, the dissolution effect of DBU / COS / DMSO system on cellulose is significantly better than that of the other three.
[0137] Embodiment 25:
[0138] Weigh 7 wt % of microcrystalline cellulose, 2.828 g of an organic base 1,8-diazabicyclo[5.4.0]-7-undecene (DBU), and the balance of an organic solvent dimethyl sulfoxide (DMSO), mix them, add them into a reactor, and cover the reactor;
[0139] 1.0 MPa of COS gas was charged into the reactor and stirred for reaction at 30° C. for 4 h to obtain a homogeneous cellulose solution.
[0140] Embodiment 26:
[0141] The reaction conditions of this example are consistent with those of Example 21;
[0142] The difference is that the mass concentration of cellulose in this embodiment is 10wt%.
[0143] Embodiment 27:
[0144] The reaction conditions of this example are consistent with those of Example 21;
[0145] The difference is that the mass concentration of cellulose in this embodiment is 12 wt %.
[0146] Embodiment 28:
[0147] The reaction conditions of this example are consistent with those of Example 21;
[0148] The difference is that the mass concentration of cellulose in this embodiment is 15wt%.
[0149] The COS gas in the reaction kettle of Examples 25-28 was released, and then the microscopic morphology of the cellulose solution was observed using polarized light. The relevant results are shown in Table 4 below:
[0150] Table 4
[0151] serial number Cellulose content wt% Organic base Organic solvents polarized light 25 7 DBU DMSO + 26 10 DBU DMSO - 27 12 DBU DMSO - 28 15 DBU DMSO -
[0152] Note: “-” indicates incomplete dissolution, “+” indicates complete dissolution
[0153] The results fully demonstrate that when DMSO with a greater polarity and DBU with a stronger alkalinity are used as the solvent, cellulose has a good dissolution effect and the maximum dissolution concentration reaches 7wt%.
[0154] Embodiment 29:
[0155] Weigh 5 wt % of microcrystalline cellulose, 15 wt % of an organic base 1,8-diazabicyclo[5.4.0]-7-undecene (DBU), and the balance of an organic solvent dimethyl sulfoxide (DMSO), then mix them and add them into a reactor, and cover the reactor;
[0156] 1.0 MPa of COS gas was charged into the reactor and stirred for reaction at 30° C. for 4 h to obtain a homogeneous cellulose solution.
[0157] Embodiment 30:
[0158] The reaction conditions of this example are consistent with those of Example 25;
[0159] The difference is that the cellulose in this embodiment is cotton pulp cellulose.
[0160] Embodiment 31:
[0161] The reaction conditions of this example are consistent with those of Example 25;
[0162] The difference is that the cellulose in this embodiment is bamboo pulp cellulose.
[0163] Embodiment 32:
[0164] The reaction conditions of this example are consistent with those of Example 25;
[0165] The difference is that the cellulose in this embodiment is corn stalks.
[0166] The COS gas in the reaction kettle of Examples 29-32 was released, and then the microscopic morphology of the cellulose solution was observed using polarized light. The relevant results are shown in Table 5 below:
[0167] Table 5
[0168] serial number Cellulose content wt% Organic base Organic solvents Cellulose polarized light 29 5 DBU DMSO Microcrystalline Cellulose + 30 5 DBU DMSO Cotton pulp cellulose - 31 5 DBU DMSO Bamboo pulp cellulose - 32 5 DBU DMSO Corn stalks -
[0169] Note: “-” indicates incomplete dissolution, “+” indicates complete dissolution
[0170] This conclusion fully demonstrates that when the degree of polymerization of cellulose increases, the dissolution effect of the new DBU / COS / DMSO solvent system on cellulose is significantly reduced.
[0171] Embodiment 33
[0172] Weigh 1 g of microcrystalline cellulose, 2.828 g of 1,8-diazabicyclo[5.4.0]-7-undecene (DBU) and 15.367 g of dimethyl sulfoxide (DMSO) into the reactor, and cover the reactor;
[0173] The reactor was charged with 1.0 MPa of COS gas, and then heated to 30°C and stirred for 4 hours to obtain a homogeneous cellulose solution.
[0174] Methylacrylate was added by an in-situ feeding device, and the molar ratio of the C=C bond in the methacrylate to the glucose unit in the cellulose solution was controlled to be 3:1. The reaction was carried out at 30°C for 2 hours to obtain a reddish-brown homogeneous solution. The reaction solution was added dropwise into anhydrous ethanol at a rate of 1-2 drops / s while stirring. The precipitate was filtered and washed with 200 mL of ethanol for 2-3 times, and dried in a vacuum oven at 60°C for 48 hours to obtain a sulfur-containing cellulose functional material.
[0175] Embodiment 34
[0176] The reaction conditions of this example are consistent with those of Example 33;
[0177] The difference is that the acrylate compound in this embodiment is phenethyl acrylate.
[0178] Embodiment 35
[0179] The reaction conditions of this example are consistent with those of Example 33;
[0180] The difference is that the acrylate compound in this embodiment is 4-formyl-2-methoxyphenyl acrylate.
[0181] The products of the coupling reactions of different acrylate compounds in Examples 33-35 were tested, and the relevant results are shown in Table 5 below:
[0182] Table 6
[0183] serial number Acrylate compounds Degree of substitution Yield 33 Methacrylate 1.15 86 34 Phenylethyl acrylate 0.84 80 35 4-Formyl-2-methoxyphenyl acrylate 0.68 71
[0184] This example fully illustrates that different acrylate compounds can undergo coupling reaction with the cellulose solution of the present invention.
[0185] Embodiment 36
[0186] Weigh 1 g of microcrystalline cellulose, 2.828 g of 1,8-diazabicyclo[5.4.0]-7-undecene (DBU) and 15.367 g of dimethyl sulfoxide (DMSO) into the reactor, and cover the reactor;
[0187] The reactor was charged with 1.0 MPa of COS gas, and then heated to 30°C and stirred for 4 hours to obtain a homogeneous cellulose solution.
[0188] Methylacrylate was added by an in-situ feeding device, and the molar ratio of the C=C bond in the methacrylate to the glucose unit in the cellulose solution was controlled to be 2:1. The reaction was carried out at 25°C for 3 hours to obtain a reddish-brown homogeneous solution. The reaction solution was added dropwise into anhydrous ethanol at a rate of 1-2 drops / s while stirring. The precipitate was filtered and washed with 200 mL of ethanol for 2-3 times, and dried in a vacuum oven at 60°C for 48 hours to obtain a sulfur-containing cellulose functional material.
[0189] Embodiment 37
[0190] Weigh 1 g of microcrystalline cellulose, 2.828 g of 1,8-diazabicyclo[5.4.0]-7-undecene (DBU) and 15.367 g of dimethyl sulfoxide (DMSO) into the reactor, and cover the reactor;
[0191] The reactor was charged with 1.0 MPa of COS gas, and then heated to 30°C and stirred for 4 hours to obtain a homogeneous cellulose solution.
[0192] Methylacrylate was added by an in-situ feeding device, and the molar ratio of the C=C bond in the methacrylate to the glucose unit in the cellulose solution was controlled to be 1:1. The reaction was carried out at 35°C for 1 hour to obtain a reddish-brown homogeneous solution. The reaction solution was added dropwise into anhydrous ethanol at a rate of 1-2 drops / s while stirring. The precipitate was filtered and washed with 200 mL of ethanol for 2-3 times, and dried in a vacuum oven at 60°C for 48 hours to obtain a sulfur-containing cellulose functional material.
[0193] Embodiment 38
[0194] 10 mg of sulfur-containing functional cellulose in Example 33 was weighed into 5 40 mL glass bottles, and then 20 mL of 500 ppm copper chloride, mercuric chloride, chromium chloride, zinc chloride, and cadmium chloride solutions were measured into 5 bottles, respectively. The solutions were shaken at room temperature for 24 hours, and then the removal rates were analyzed by ACP tester. The corresponding test results are shown in the following table:
[0195] Table 7
[0196] serial number heavy metal solution Adsorption time (h) Removal rate (%) 36 Mercuric chloride 24 99.6 37 Cupric chloride 24 25.2 38 Zinc chloride 24 11.7 39 Chromium chloride 24 22.9 40 Cadmium chloride 24 23.3
[0197] This example illustrates that the product after the acrylate-COS-cellulose multi-component coupling reaction has a good adsorption effect on heavy metals, especially a better removal effect on mercury ions.
[0198] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a cellulose solution, characterized in that: A mixture of organic alkali, COS and organic solvent is used as a dissolving system to dissolve cellulose.
2. The method for preparing a cellulose solution according to claim 1, characterized in that: The method comprises the following steps: (1) mixing cellulose, an organic base and an organic solvent to obtain a mixture; (2) placing the mixed material in a reaction kettle, filling it with COS gas and sealing it; (3) heating the sealed reactor to react the mixture therein, and obtaining a cellulose solution after the reaction is completed.
3. The method for preparing a cellulose solution according to claim 1 or 2, characterized in that: The cellulose is one of microcrystalline cellulose, cotton, wood pulp, bamboo pulp or straw cellulose, or a combination of any of them; The cellulose has the following general chemical structure: Among them, 50﹤n-4﹤1000; The organic base is any one of the following structures: Wherein: R is independently H, methyl or ethyl; R1 is independently H or -CH3; R2, R3, R4 and R5 are independently H or alkyl with 1-6 carbon atoms; The organic solvent is one of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylimidazolidinone, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide or N,N-dimethylpropylene urea, or a mixture of any of them.
4. The method for preparing a cellulose solution according to claim 2, characterized in that: In the mixed material of step (1), the mass concentration of cellulose is 1-20%, the mass concentration of organic base is 0.5-30%, and the balance is organic solvent.
5. The method for preparing a cellulose solution according to claim 2, characterized in that: In the sealed reactor described in step (2), the pressure of COS gas is 0.2-5 MPa.
6. The method for preparing a cellulose solution according to claim 2, characterized in that: The final heating temperature in step (3) is 30-70°C, and the reaction time is 2-6h.
7. A sulfur-containing cellulose functional material, characterized in that: The method is prepared by using the cellulose solution obtained by the method according to any one of claims 1 to 6 and an acrylate compound as raw materials, wherein the acrylate compound is any one of the following compounds: Wherein: R is independently -CH3 or an alkyl group with 1-6 carbon atoms.
8. The sulfur-containing cellulose functional material according to claim 7, characterized in that: The preparation method comprises adding an acrylic acid ester compound to the cellulose solution, reacting at 25-35°C for 1-3h, then adding the reaction product to anhydrous ethanol, stirring to obtain a precipitate, and finally filtering out the precipitate, washing it with ethanol, and then drying it to obtain a heavy metal ion adsorbent in the solution.
9. The sulfur-containing cellulose functional material according to claim 8, characterized in that: When the acrylic acid ester compound is added to the cellulose solution, the molar ratio of the glucose unit in the cellulose solution to the C=C bond in the acrylic acid ester compound is 1:1-3.
10. Application of the sulfur-containing cellulose functional material according to any one of claims 7 to 9 in the fields of wastewater treatment, biomedicine, electronics industry and coating industry.
Citation Information
Patent Citations
Preparation method of cellulose membrane material in novel dissolving system
CN109880135A
Method for dissolving cellulose and regenerated cellulose
CN117946421A
Preparation of sulfydryl and disulfide bond functionalized cellulose ester material, material and application
CN118108864A
